The Outstanding Beneficial Roles of Irisin in Depressive Disorders - Algül, Sermin; Ilcin, Saadet; Ozcelik, Oguz (VM Media SP. zo.o VM Group SK, 2021)
Objective: Depression is a widely observed psychiatric disorder that affects a quite large number of people all around the world. A major depressive disorder (MDD) is a multifactorial disease that associated with fluctation in appetite, body weight, and energy situations in addition to serious mood problems. The aim of this review is concentrated to investigate possible link between energy regulatory hormones of irisin and depressive disorders. Methods: Irisin is a hormone that has significant contribution to the regulation of lipid and glucose metabolism in skeletal muscle and adipose tissue. Results: Irisin was also reported to have significant roles in central nervous system. In the literature, there are reports indicating the beneficial antidepressant role of irisin in MDD. Conclusions: It should be emphsesied that the antidepressive effects of exercise could be the results of exercise induced increased hormones of irisin.
Keywords: 3. Good health